(untitled) (Medico Legal Update, 2021)
The research objectives to reveal the effect of the physical and artistic education lesson during play and art to develop some motor abilities and reduce hyperkinetic among fifth grade pupils. The researchers used the experimental approach, and the research sample consisted of (66) students and (10) students in each group, and about By drawing lots, two groups were named to represent one of them the experimental group and the other the control group, and parity was achieved between the two groups in the variables (age, weight, and height) as well as achieving parity between them in terms of motor abilities (under study) and their hypermobility, and playing and practicing technical drawings with Pupils of the experimental group As for the control group, the method used by the teacher was used, and the implementation of the experiment took nine weeks with two educational units per week for each group of 18 educational units, and the time of one educational unit reached (45) minutes, and the implementation of the experiment was started. On Sunday, 10/2/2018, until Thursday, January 14, 2019. After analyzing the data statistically, the researchers reached the following two conclusions: 1. Learning by playing and art during the physical and artistic education lesson had a clear role in developing some of the experimental group’s motor abilities. 2. The learning style by playing and art collectively led to the reduction of hyperactivity and distraction, and the formation of good relationships between them.